Bidirectional learning opportunities: How GP‐supervisors and trainees exchange knowledge. Issue 12 (16th July 2021) - Welink, Lisanne S.; van Charldorp, Tessa C.; Di Colandrea, Laura; Bartelink, Marie‐Louise L.; Pype, Peter; Damoiseaux, Roger A.M.J.; de Groot, Esther
Abstract: Introduction: Workplace‐based learning conversations can be a good opportunity for supervisors and trainees to learn from each other. When both professionals discuss their specific knowledge openly with each other, learning conversations may be a useful educational tool, for instance for learning how to apply evidence‐based medicine (EBM) in the workplace. We do, however, need a better understanding of how the exchange of knowledge provides opportunities for such bidirectional learning. The aim of this study was therefore to analyse how trainees and supervisors currently handle bidirectional learning opportunities by describing in detail how supervisors respond to knowledge expressed by trainees during a learning conversation. Method: We video‐recorded learning conversations between supervisors and trainees in general practice (GP). Within these learning conversations, EBM discussions on medical topics were selected and transcribed. We then identified, analysed using Conversation Analysis (CA) and categorised each expression of knowledge by the trainee and the supervisor's subsequent response. Results: We found that when a trainee expresses knowledge during the learning conversation, supervisors either (a) refute the expressed knowledge, (b) immediately suggest an alternative or (c) pose (additional) questions. These responses have consequences for the learning opportunities of both trainee and supervisor: it is only when supervisors pose further questions that trainees are encouraged to elaborate on their knowledge, leading to a bidirectional learning opportunity. Discussion: Improving EBM learning opportunities for both supervisors and trainees requires more than simply instructing trainees to express knowledge‐based—for instance—on recent evidence more often. Inflexible institutional roles related to historical claims of supervisors' epistemic authority hamper bidirectional learning. Posing open questions during learning conversations enhances the flexibility of institutional roles while also creating bidirectional learning opportunities. Abstract : In workplace‐based conversations, supervisors can respond to trainees' utterances of knowledge by refuting, suggesting alternatives, or posing questions. Only the latter leads to bidirectional learning opportunities.